Surgical Evaluation of P-Possum and Cr-Possum Scores in Patient Undergoing Colorectal Cancer Operation (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: "Portsmouth" modification of POSSUM (P-POSSUM) scoring system used to assess mortality in general surgical patients and “Colorectal” Cr-POSSUM scoring system used for mortality assessment for colorectal patient.Objective: The purpose of the present study was to estimate the validity of the P-POSSUM (Portsmouth-POSSUM) and Cr-POSSUM (Colorectal-POSSUM) score in predicting the risk of mortality in colorectal cancer patient.Methodology: This was single centre clinical trial was carried out in the Department of Surgery at Dhaka Medical College Hospital, Dhaka, Bangladesh from November 2013 to April 2014 for a period of six (06) months. Patients of both sex who got admitted in the surgery in-patient department for elective colorectal cancer operations were selected as study population. Both the P-POSSUM and Cr-POSSUM, physiological score, operative score, predicted mortality rate were calculated using an online POSSUM calculator. Based on both P-POSSUM and Cr-POSSUM Scoring, patients were categorized into three risk groups. Then a comparative analysis was performed between the observed and the predicted values as well as the Observed/Predicted ratio (O:P) in all the risk groups.Results: A total of 50 patients with the median age of 50 (ranging 20 to 72) years were studied. 30 days overall observed mortality was 3(6%) patients. The mean P-POSSUM and C-POSSUM physiological scores were 32.49±2.08 and 13.92±1.30 respectively. However, the operative score was 11.59±1.46 and 8.12±0.24 in P-POSSUM and C-POSSUM respectively. The overall mortality predicted by the P-POSSUM model was 5 patients (19.33±2.87) and mortality predicted by the Cr-POSSUM model was 4 patients (20.66±4.09).Conclusion: In conclusion both model accurately predicted the risk of postoperative death. Cr-POSSUM provided a better fit to observed results than P-POSSUM.Journal of National Institute of Neurosciences Bangladesh, 2020;6(2): 118-123